The visibility of modernization in architecture
1 online resource.
Keywords: "This edited collection explores the visibility of modernization in architecture produced in different capitalist regions across the world and provides readers with a historico-theoretical and historico-geographical discussion. Focusing on a particular building type, an influential architect's work, as well as relevant texts and documents, each chapter addresses the many facets of "delay" which are central to the problematization of capitalism's progressive dissemination of technological and aesthetic regimes of modernism. This collection underlines the centrality of temporality for a critical understanding of colonialism, modernism, and capitalism. The book is primarily concerned with the historical timeline, the tangential point when a nation enters modernization processes. In exploring modernism in diverse regions such as East Asia, Pacific, Eastern Europe, and Iran, each chapter addresses the historiographic and architectonic unfolding of modernization beyond the western hemisphere. The exploration of these diverse case-studies will be of interest to students of architecture and researchers working on the collision of temporalities and the subject's critical importance for different country's built-environments"--